A review on the flow structure and pollutant dispersion in urban street canyons for urban planning strategies. (August 2014) - Yazid, Afiq Witri Muhammad; Sidik, Nor Azwadi Che; Salim, Salim Mohamed; Saqr, Khalid M
As a result of rapid urbanization in numerous cities around the world, the demand for transportation has increased rapidly, resulting in emission of high levels of exhaust pollutants into the atmosphere. This is a major cause of deterioration in the local air quality, with consequent escalating risk of adverse health conditions amongst urban inhabitants. Understanding dispersion of pollutants in street canyons, local urban configurations, meteorological processes, and other physical factors are essential for predicting and assessing air quality. This article presents a comprehensive review of the state-of-the-art research works relevant to the investigation of flow structures and pollutant dispersion phenomena in urban street canyons. Various factors, including building geometries, local atmospheric conditions, static and dynamic obstructions, as well as chemical reactions of exhaust pollutants, are critically discussed by taking into account field measurements, wind tunnel experiments, operational modeling techniques, and computational fluid dynamics (CFD). The most critical pollutant levels in street canyons under several physical circumstances are identified. Elements leading to discrepancies and resulting in inconsistencies of different research methods are briefly addressed and suggestions for future research are offered.